ANSWERING THE CHALLENGES AND POTENTIAL DEVELOPMENT OF ISLAMIC INSURANCE IN INDONESIA: MENJAWAB TANTANGAN DAN POTENSI PERKEMBANGAN ASURANSI SYARIAH DI INDONESIA - Ichwan Ahnaz Alamudi (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
ABSTRACT This article is motivated by a large market share that reflects the very high interest of the Indonesian people in sharia insurance. Unfortunately, this great interest in Islamic financial products is sometimes not responded to by the Islamic insurance industry. In fact, the existence of Islamic insurance will make it possible to accelerate the rate of growth. This article uses literature data or library research with juridical-normative type. In this paper the author produces sharia insurance is a concept in which there is mutual risk among fellow participants. Thus, one another becomes the insurer of the risks that arise. This mutual risk-bearing is done on the basis of mutual assistance in kindness by each issuing tabarru' funds or benevolent funds (charity). Furthermore, Islamic insurance has the advantage of fulfilling a sense of justice making it an opportunity to grow, the concept of profit sharing in Islamic insurance where the amount is divided according to the proportion of the results obtained so that no one is harmed. Therefore, many conventional insurance companies have begun to look at the products of Islamic insurance. Keywords: Development, Law, Islamic Insurance.